An unusual case of large epidermoid inclusion cystic lesion in the floor of the mouth causing double chin appearance - Satnam Singh (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2020)
Epidermal inclusion cyst is painless, rare slow-growing swelling in midline due to the inclusion of ectodermal tissue into unusual sites. These cysts are covered under the teratomas category due to the absence of skin appendages within their squamous epithelium-lined thin walls. Testes and ovaries are the common sites of occurrence of epidermal cysts [1]. In the head and neck region these are mostly seen in the lateral third of the eyebrows.